STRATEGI PRODUKSI MINI SERIES BERBASIS SOSTAC PADA KAMPANYE DIGITAL PROGRAM KAMPUS INKLUSI REELS INSTAGRAM @DITJEN_DIKTI - Larasati Maharani; Hudi Santoso (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
This study aims to design a concept for producing a mini-series as a digital campaign for the Inclusive Campus program on Instagram Reels @ditjen_dikti and to analyze the application of the SOSTAC model in the production process, including the role of the producer. This study employs a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. Informants were selected through purposive sampling, involving students with disabilities at IPB University—Putri Najla Rasyidah and Rama Vijaya Jhowry—as well as institutional representatives serving as supporting sources. The results indicate that the campaign was produced in three episodes and distributed via Instagram Reels in collaboration with @ipbofficial. The SOSTAC model was systematically applied from planning through evaluation. The campaign employed a participant-driven storytelling approach, showcasing the real-life experiences of students with disabilities, reinforced by perspectives from the campus environment and their families. Evaluation results indicate that the message of an inclusive campus was conveyed consistently, although limitations remain regarding production flexibility, issue diversity, and audience engagement optimization. This study also demonstrates that digital media can effectively serve as a medium for conveying messages of inclusion to the broader public. Keywords: Digital Campaign, Inclusive Campus, Mini Series, Producer, SOSTAC